2005
DOI: 10.1029/2005jc002945
|View full text |Cite
|
Sign up to set email alerts
|

Average circulation, seasonal cycle, and mesoscale dynamics of the Peru Current System: A modeling approach

Abstract: [1] The Humboldt Current System is the most productive of the eastern boundary currents. In the northern part, the Peru Current System (PCS) is located between 5°S and 20°S. Along the Peruvian coast, an equatorward wind forces a strong coastal upwelling. A high resolution model is designed to investigate the mean circulation, the seasonal cycle, and the mesoscale dynamics for the PCS. The model is able to reproduce the equatorward Peru Coastal Current (PCC), the Peru Chile Under-Current (PCUC) which follows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
281
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(311 citation statements)
references
References 43 publications
19
281
2
1
Order By: Relevance
“…The former are based on the calculation of some dynamic fields and define eddies based on the 10 closed contours of a threshold value. The physical fields computed are SLA, Sea Surface Height (SSH) Chaigneau et al, 2009), vorticity (McWilliams, 1999 and velocity gradient tensor or Okubo-Weiss parameter (W) (Penven and Echevin, 2005;Chelton et al, 2007;Isern-Fontanet and E. Garcìa-Ladona, 2003 are based on the curvature or shape of the instantaneous flow field. Several studies make use of both physical and geometrical methods to better explain the structure of mesoscale eddies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former are based on the calculation of some dynamic fields and define eddies based on the 10 closed contours of a threshold value. The physical fields computed are SLA, Sea Surface Height (SSH) Chaigneau et al, 2009), vorticity (McWilliams, 1999 and velocity gradient tensor or Okubo-Weiss parameter (W) (Penven and Echevin, 2005;Chelton et al, 2007;Isern-Fontanet and E. Garcìa-Ladona, 2003 are based on the curvature or shape of the instantaneous flow field. Several studies make use of both physical and geometrical methods to better explain the structure of mesoscale eddies.…”
Section: Methodsmentioning
confidence: 99%
“…This was done through a series of eulerian statistics (performed on a regular grid) computed on the output of the lagrangian tracking method adopted. The automated detection and tracking method used is a hybrid method (combination of the physical and the geometrical approaches) performed by Penven and Echevin (2005) and Halo et al (2014), and it is detailed in the following section. Such method was applied on a long-term time series (22 years) of daily SLA fields, so providing a robust basis for statistical analysis.…”
mentioning
confidence: 99%
“…In this study eddies were tracked in space and consecutive time-steps with reference to the centres of eddies, in a generalized non-dimensional property space, following the method proposed by Penven et al (2005). The tracking scheme assumes that an identified eddy centre detected in a first frame is the same eddy in the subsequent frame if the generalized distance in the non-dimensional property space is minimum.…”
Section: Hybrid Eddy Detection Algorithmmentioning
confidence: 99%
“…In this context the strength of the PCUC is essential (Thomsen et al, 25 2016). Observations as well as models show a weak seasonal variability of the PCUC off Peru which is stronger in austral summer and fall (Thomsen et al, 2016;Chaigneau et al, 2013;Penven et al, 2005) Ocean Sci. Discuss., https://doi.org/10.5194/os-2018-5 Manuscript under review for journal Ocean Sci.…”
Section: General Eddy Generation and Its Seasonal Cycle In The Etspmentioning
confidence: 99%
“…ASA is even negative in 2015 due to the strong doming in the upper 200 m. As both mode-water eddies have about the same propagation speed and 25 volume, the differences of water mass properties point towards seasonal or interannual variations of the water mass characteristics during their formation. The MWE is generated in February, when upwellingfavorable alongshore winds weaken and SST increases (Gutiérrez et al, 2011), whereas the mode-water Stramma et al (2014) is generated in April, when the PCUC, which transports oxygen-deficient ESSW (Hormazabal et al, 2013), has its poleward maximum (Shaffer et al, 1999;Penven et al, 2005;Chaigneau et al, 2013). Additionally, the mode-water eddy observed by Stramma et al (2014) was generated in year 2011, which is considered as a La Niña-period, when generally lower oxygen and higher salinity values exist in the upper 100 m depth (Stramma et al, 2016) leading 5 to higher anomalies of salt and oxygen of the MWE observed by Stramma et al (2014) in comparison to the actual MWE.…”
Section: Net Transport Of Heat Salt and Oxygen Via Eddies In The Etspmentioning
confidence: 99%